Combined Effect of High-Pressure Processing with Spice Extracts on Quality of Low-Salt Sausage during Refrigerated Storage - Qing Xiao (MDPI AG, 2021)
The study evaluated the combined effect of high-pressure processing (HPP) and spice extracts on low-salt sausages during refrigerated storage. Physicochemical and microbiological characteristics of the sausages were determined. HPP treatment increased the thiobarbituric acid reactive substances (TBARS) value and the carbonyl content of the samples (p < 0.05), which meant lipid and protein oxidation was accelerated. Adding clove and cinnamon extracts can retard the oxidation caused by HPP (p < 0.05). The pH of the sausages treated with both the spice extracts and HPP maintained a higher pH value during the storage (p > 0.05). Compared with the samples treated with HPP or with the spice extracts alone, the combined treatment observably inhibited the growth of spoilage bacteria (p < 0.05) and improved the microbial community. The results demonstrated that the use of clove and cinnamon extracts in conjunction with HPP improved the storage quality and prolonged the shelf-life of the low-salt sausages. Thus, the combined use of spice extracts and HPP can be developed as a promising way to preserve low-salt meat products.